1996
DOI: 10.1177/112067219600600106
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Profile of Brimonidine

Abstract: Brimonidine is a selective alpha 2-adrenergic agonist developed for lowering intraocular pressure in glaucoma patients. Since brimonidine will be used in long-term theraphy, the safety of this drug is an important feature for its clinical success. Brimonidine has been evaluated in a number of safety studies using doses much greater than those in humans. In this paper chronic and carcinogenicity studies are presented. The results of the 6-month ocular/systemic study in rabbits and the 1-year ocular/systemic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Aside from exaggerated pharmacology, brimonidine was not associated with toxicity in rabbits or monkeys after chronic ocular administration . Brimonidine was reported not to be carcinogenic after oral administration to mice and rats and induced only hypertrophy of the tunica muscularis and hyperplasia of the intestine in rodents after oral administration . Brimonidine is not genotoxic and not teratogenic or a reproductive toxicant .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Aside from exaggerated pharmacology, brimonidine was not associated with toxicity in rabbits or monkeys after chronic ocular administration . Brimonidine was reported not to be carcinogenic after oral administration to mice and rats and induced only hypertrophy of the tunica muscularis and hyperplasia of the intestine in rodents after oral administration . Brimonidine is not genotoxic and not teratogenic or a reproductive toxicant .…”
Section: Introductionmentioning
confidence: 96%
“…Brimonidine is 1000‐fold more selective to α 2A ‐adrenoceptor ( α 2 AR), as compared to the α 1 ‐adrenoceptor ( α 1 AR) and is 7–12‐fold more selective to α 2 AR than the reference compound clonidine . Pharmacological effects of brimonidine include lowering of the intraocular pressure, vasoconstriction and protection of the optic nerve from secondary damage following injuries and the drug can induce sinus bradycardia, sedation, slight hypotension and sinus arrhythmia after oral administration to monkeys . Aside from exaggerated pharmacology, brimonidine was not associated with toxicity in rabbits or monkeys after chronic ocular administration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, drug binding to melanin has potential implications, such as the generation of a depot or slow-release site, which may explain the higher concentrations of drug in the vitreous humor of rabbits and monkeys following chronic dosing (Table 1). Long-term studies with 0.5 and 0.2% brimonidine have shown that chronic treatment with brimonidine is safe (Angelov et al, 1996), suggesting that there are no detrimental effects of brimonidine binding to melanin. In the ocular samples subjected to HPLC analysis (including the conjunctiva, iris, ciliary body, and aqueous humor from both monkeys and rabbits), 65 to 100% of the radioactivity represented intact brimonidine.…”
Section: Ocular Distribution Of Brimonidinementioning
confidence: 99%
“…Extensive systemic and ocular safety assessment studies in animal models have demonstrated a large safety margin of brimonidine (Angelov et al 1996;Walters 1996).…”
Section: Introductionmentioning
confidence: 99%